2007
DOI: 10.1084/jem.20062694
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinating enzyme CYLD negatively regulates the ubiquitin-dependent kinase Tak1 and prevents abnormal T cell responses

Abstract: The deubiquitinating enzyme CYLD has recently been implicated in the regulation of signal transduction, but its physiological function and mechanism of action are still elusive. In this study, we show that CYLD plays a pivotal role in regulating T cell activation and homeostasis. T cells derived from Cyld knockout mice display a hyperresponsive phenotype and mediate the spontaneous development of intestinal inflammation. Interestingly, CYLD targets a ubiquitin-dependent kinase, transforming growth factor–β-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
223
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(234 citation statements)
references
References 51 publications
8
223
0
3
Order By: Relevance
“…In the present study, we identified TAK1 as the target of CYLD in inhibitions of MKK3-p38 MAPK pathway. Our finding is in line with recent reports that demonstrated that TAK1 polyubiquitination is involved in its activation and TAK1 interacts with and is deubiquitinated by CYLD to prevent the excessive activation of T cells (41,42). In summary, the present study identifies CYLD as a negative regulator for NFAT by deubiquitinating TAK1 and provides novel and interesting insights into the molecular pathogenesis of S. pneumoniae infection.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, we identified TAK1 as the target of CYLD in inhibitions of MKK3-p38 MAPK pathway. Our finding is in line with recent reports that demonstrated that TAK1 polyubiquitination is involved in its activation and TAK1 interacts with and is deubiquitinated by CYLD to prevent the excessive activation of T cells (41,42). In summary, the present study identifies CYLD as a negative regulator for NFAT by deubiquitinating TAK1 and provides novel and interesting insights into the molecular pathogenesis of S. pneumoniae infection.…”
Section: Discussionsupporting
confidence: 81%
“…5C, knock down of CYLD by siRNA exhibited no inhibitory effect on calcineurin activity. Because recent reports demonstrated that TAK1 polyubiquitination is involved in its activation and TAK1 interacts with and is deubiquitinated by CYLD to prevent the excessive activation of T cells (41,42), we sought to determine whether CYLD acts as a negative regulator for S. pneumoniaeinduced NFAT signaling through deubiquitinating TAK1. We first determined whether S. pneumoniae induces TAK1 polyubiquitination.…”
Section: S Pneumoniae Activates Nfat Through Camentioning
confidence: 99%
“…6, B and D). These include transforming growth factor ␤-activated kinase 1 (TAK1), TAK1-binding proteins 1-3 (TAB1-3), NF-B essential modulator (NEMO), and deubiquitinating enzymes such as A20 and cylindromatosis tumor suppressor protein (CYLD) (27,(52)(53)(54)(55)(56). Among these, Li et al reported that AMPK␣2 associates with TAB1 and activates p38 MAPK in mouse heart (57).…”
Section: Discussionmentioning
confidence: 99%
“…6E). As IB␣ is degraded by the ubiquitin process after phosphorylation (24 -26), these findings suggest that IB␣ might undergo chronic degradation and resynthesis in AMPK␣ Ϫ/Ϫ ⌴⌭Fs and that the AMPK␣ deletion causes constitutive activation of the NF-〉 pathway in MEFs (27).…”
Section: -Foldmentioning
confidence: 99%
“…and Cyld ϩ/ϩ littermates, and genotyping was performed by PCR using tail DNA (30). All mice were housed in specific pathogen-free cages and monitored periodically (every 3 months) for the lack of common pathogens.…”
Section: Methodsmentioning
confidence: 99%